Priming xylem for stress recovery depends on coordinated activity of sugar metabolic pathways and changes in xylem sap pH. (8th March 2019) - Pagliarani, Chiara; Casolo, Valentino; Ashofteh Beiragi, Maryam; Cavalletto, Silvia; Siciliano, Ilenia; Schubert, Andrea; Gullino, Maria Lodovica; Zwieniecki, Maciej A.; Secchi, Francesca
Abstract: Some plant species are capable of significant reduction of xylem embolism during recovery from drought despite stem water potential remains negative. However, the functional biology underlying this process is elusive. We subjected poplar trees to drought stress followed by a period of recovery. Water potential, hydraulic conductivity, gas exchange, xylem sap pH, and carbohydrate content in sap and woody stems were monitored in combination with an analysis of carbohydrate metabolism, enzyme activity, and expression of genes involved in sugar metabolic and transport pathways. Drought resulted in an alteration of differential partitioning between starch and soluble sugars. Upon stress, an increase in the starch degradation rate and the overexpression of sugar symporter genes promoted the efflux of disaccharides (mostly maltose and sucrose) to the apoplast. In turn, the efflux activity of the sugar‐proton cotransporters caused a drop in xylem pH. The newly acidic environment induced the activity of apoplastic invertases leading to the accumulation of monosaccharides in the apoplast, thus providing the main osmoticum necessary for recovery. During drought and recovery, a complex network of coordinated molecular and biochemical signals was activated at the interface between xylem and parenchyma cells that appeared to prime the xylem for hydraulic recovery. Abstract : A successful restoration of xylem function requires a coordinated activity of multiple biological processes involving sugar metabolism and transport. This activity, triggered during drought stress, leads to prime xylem recovery by efflux of monosaccharides in the apoplast under low pH conditions.